2022
DOI: 10.1177/1759720x221079256
|View full text |Cite
|
Sign up to set email alerts
|

Measuring sedentary behavior using waist- and thigh-worn accelerometers and inclinometers – are the results comparable?

Abstract: Background: Objective sensor-based quantification of sedentary behavior is an important tool for planning and evaluating interventions for excessive sedentary behavior in patients with musculoskeletal diseases. Although waist-worn accelerometers are the standard for physical activity (PA) assessment, only thigh-worn inclinometers can clearly distinguish sedentary behavior from any light PA or standing activity. Methods: In this study, 53 adults (ages 20–85 years) wore two ActiGraph wGT3X-BT monitors, each cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The fat mass index (FMI) was calculated as the total body fat weight (kg) divided by height in meters squared. 26 The visceral fat area was estimated by multiplying the visceral fat rating, based on the TANITA device manufacturer guidelines, 27 by 10.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fat mass index (FMI) was calculated as the total body fat weight (kg) divided by height in meters squared. 26 The visceral fat area was estimated by multiplying the visceral fat rating, based on the TANITA device manufacturer guidelines, 27 by 10.…”
Section: Methodsmentioning
confidence: 99%
“… 19 However, such waist/hip-worn devices may have relatively low accuracy in identifying sedentary behavior. 27 , 28 Furthermore, there may be more discomfort while sleeping or embarrassment with device visibility 29 compared with wrist- or thigh-worn devices. Meanwhile, thigh-worn accelerometers are valid tools for assessing changes in posture and PAs.…”
Section: Introductionmentioning
confidence: 99%
“…In this cross-sectional validation study, we used some data from a previously conducted study that tested the accuracy of accelerometry and inclinometry for the detection of SB in 53 adults. Briefly, we demonstrated that not only inclinometry via thigh-worn devices, but also accelerometry via waist-worn devices can be used to reliably assess SB if appropriate technical settings are used [17].…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Consequently, researchers should exercise caution when considering the utilization of the inclinometer function of hip-worn accelerometers, particularly in studies emphasizing the duration of SB [17]. The inclinometer function is sensitive to factors such as body shape, because the amount and distribution of body fat can alter the tilting angles of the inclinometer [18,19]. Thus, BMI has an additional impact on the measurement of sitting time using the inclinometer function of accelerometers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, BMI has an additional impact on the measurement of sitting time using the inclinometer function of accelerometers. Individuals with higher BMI tend to sit more, but BMI is associated with body shape and composition, which may compromise the ability of hip-worn accelerometers to accurately detect body postures [18]. The recent developments in the field of hip-worn accelerometer algorithms have made it possible to quantify SB as per the proper definition.…”
Section: Introductionmentioning
confidence: 99%